2011
DOI: 10.1186/1475-2891-10-74
|View full text |Cite
|
Sign up to set email alerts
|

Chronologically scheduled snacking with high-protein products within the habitual diet in type-2 diabetes patients leads to a fat mass loss: a longitudinal study

Abstract: BackgroundObesity is the most relevant overnutrition disease worldwide and is associated to different metabolic disorders such as insulin resistance and type-2 diabetes. Low glycemic load foods and diets and moderately high protein intake have been shown to reduce body weight and fat mass, exerting also beneficial effects on LDL-cholesterol, triglyceride concentrations, postprandial glucose curve and HDL-cholesterol levels. The present study aimed at studying the potential functionality of a series of low glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Multiple studies in this review (Table 3) showed 0.8-3.3 g/kg/day greater fat loss in higher protein participants over 4–26 wk when change from habitual intake was 20.2%-35.3% [11,32,38,43]. There appeared to be three outliers in Table 3[22,33,35].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Multiple studies in this review (Table 3) showed 0.8-3.3 g/kg/day greater fat loss in higher protein participants over 4–26 wk when change from habitual intake was 20.2%-35.3% [11,32,38,43]. There appeared to be three outliers in Table 3[22,33,35].…”
Section: Discussionmentioning
confidence: 92%
“…Including weight maintenance studies would introduce a brief period where participants’ metabolisms had to adjust to an atypical intake, making “habitual protein intake” leading into the protein intervention difficult to define. Only two cross-over studies [38,56] were designed such that the habitual intake of participants prior to intervention could be determined and thus could be included in the change analysis. See the legend of Table 1 for more on study categorization.…”
Section: Methodsmentioning
confidence: 99%
“…In a 28-day high-protein low-GI diet intervention program, total cholesterol and LDL cholesterol were significantly reduced ( 43 ). But in another study, these lipid parameters did not change after 4 weeks of high-protein low-GI diets intervention ( 27 ). Our results suggest that Inzone Preload reduces total cholesterol and LDL cholesterol.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to the non-responding subgroup at baseline, the responding subgroup had a shorter duration of diabetes, higher HOMA-β level, indicating that Inzone preload may be more beneficial in less advanced diabetes. A decrease in postprandial glucose by a macro-nutrient preload might be explained by the Incretin response where increased GLP-1 can affect plasma insulin and insulin sensitivity ( 27 ). Our data also suggest that preload induced changes in 2 h-BG levels positively correlate with weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general agreement, however, that the essence of healthy ageing' is delaying the onset of the diseases of middle and advanced age un l later (op mally -much later) than the average age of onset [283]. One of the newer ideas for increasing the chances for successful ageing is chronological nutri on' -that is, staving off age-related diseases by following a nutri onal regimen based on the rhythms set by the circadian clock [284][285][286]. As was already men oned, there is significant associa on between the disrup on of circadian rhythms and the development of glucose intolerance, cardiovascular disease and cancer.…”
Section: Genotype-phenotype Correlations For Mutations and Polymorphimentioning
confidence: 99%